PELATIHAN PENYUSUNAN PERANGKAT PEMBELAJARAN BERBASIS STEM BAGI GURU SDN 6 DESA TAPAK GEDUNG - Dewi Handayani; Muzanip Alperi; Salastri Rohiat; Sura Menda Ginting (Jurnal Pengabdian Masyarakat Polmanbabel, 2023)
The challenge in 4.0 era requires teachers as part of the society to have certain qualities such as able to prepare knowledgeable and skillful students in science, technology, engineering, and mathematics (STEM) subjects as STEM based learning is align with 2013 curriculum in Indonesia. At SDN 6 Tebat Karai, teachers' ability to develop STEM-based learning tools is still lacking, so training in making and developing learning tools is needed. This activity is a community service activity aimed at elementary teachers so that they can design, prepare, and produce a set of STEM-based teaching instruments and able to perform those instruments in a classroom. The community service activity was done in SDN 06 (state elementary school) of Tebat Karai Region, Kepahiang on 28-29th of July 2023. This activity was a training program followed by 15 elementary teachers of Tebat Karai. The training method used was technical assistance method in a workshop that consisted of training, guided practice, monitoring, and evaluation processes. The output of this activity was STEM-based lesson plan using project-based learning model that consist of 6 major learning activities which are: (1) introductory by giving essential questions; (2) project planning; (3) scheduling; (4) project progress monitoring; (5) student assessment; (6) learning experience evaluation. From the activities that have been carried out, the results obtained are an increase in teacher understanding of STEM-based learning tools with a difference in N-Gain value of 0.87 in the high category.